Identity of Carex trichodes Steud. ex Boott and Carex lateriflora Phil. (subgen. Psyllophorae, sect. Junciformes, Cyperaceae) from Southern South America - Penneckamp, Diego N. (Phytotaxa, 2022)
The identity of Carex trichodes, a species only known from the collection of the type material made in 1854 is clarified after finding it in the wild in the vicinity of the type locality. It is concluded that C. trichodes was proposed based on stressed plants corresponding to the same taxon later described as C. lateriflora.